Trends in Global Higher Education - Fernández, Celestino; Finch, Jessie K.; León García, Fernando; Gárate Rivera, Alberto; Ross, Marlene (My University, 2012)
This book contains a discussion of a group of leaders, including presenters, panelists, and moderators, who contributed their expertise, shared experiences and information about higher education in their countries, enumerated trends, challenges, and innovations, and offered recommendations for future actions, initiatives, and programs. This publication summarizes their comments and their suggestions for college and university leaders to strengthen higher education around the world and to improve the educational experience of all those involved in tertiary education worldwide, especially students.
Keywords: Educación y globalización; Educación superior; Historia de CETYS; Sistemas